Experimental Study on Carbonization and Strengthening Performance of Recycled Aggregate - Mingqiang Lin; Xiang Li; Maozhi Wei; Qun Xie (Buildings)
In order to address a challenging issue in the recycling of construction debris, the impact of carbonization treatment on the characteristics of recycled aggregates (RCAs) was experimentally examined in this work. Both direct carbonization and carbonization following calcium hydroxide pretreatment were used in the study to assess the impact of carbonization on the physical characteristics of recycled aggregates. According to the findings, carbonization raised the recycled aggregates’ apparent density while drastically lowering their porosity and water absorption (by as much as 20–30%). Although the recycled aggregate’s crushing index marginally increased with age, its overall physical qualities remained excellent. Pretreatment with calcium hydroxide can improve the physical characteristics of recycled aggregates, further optimize their pore structure, and efficiently encourage the carbonation process. Furthermore, recycled aggregate’s crushing index can be considerably decreased and its quality much enhanced by the ultrasonic cavitation treatment. According to the study, the carbonation-treated recycled aggregate’s microstructure was denser in the interfacial transition zone and had a stronger link with the cement paste, improving the recycled aggregate concrete’s overall performance. XRD, infrared spectral analysis, and SEM scanning were used to determine the increased calcium carbonate content in the recycled aggregate following carbonation treatment as well as its microstructure improvement process. The findings offer fresh concepts for achieving resource efficiency and environmental preservation through the use of recycled aggregates in concrete, as well as theoretical backing for their use.